Healthy aging with parks: Association between park accessibility and the health status of older adults in urban China. (November 2018) - Xie, Bo; An, Zihao; Zheng, Yiling; Li, Zhigang
Highlights: Measuring accessibility of parks simultaneously considering the physical environment and sociopersonal context. Exploring the association between the accessibility of parks and occurrence of chronic diseases among older adults. Calling for more comprehensive economic planning strategies to improve park accessibility and promote healthy aging. Abstract: Accessibility is a crucial element reflecting the potential availability of parks. By conducting a cross-sectional study of 700 older adults sampled from 30 communities in Wuhan, China, we examine the association between the accessibility of parks and the health status of older adults. A varying two-step floating catchment area model was developed to measure the accessibility of parks for older adults that simultaneously considered the physical environment and sociopersonal context. Based on the results of a logistic regression analysis, older adults with the greatest access to parks experience significantly lower odds of cardio-cerebral vascular diseases, joint diseases and endocrine diseases than their counterparts with the least access to parks. The effects of the physical environment and sociopersonal context on the accessibility of parks and health status are also discussed. In general, these two factors jointly influence the potential alternatives to parks and participation in park-based activities among older adults and in turn affect the health benefits for older adults. This study provides empirical support for the role of parks in supporting healthy aging. It also emphasizes the need for more comprehensive economic planning strategies to improve park accessibility and promote healthy aging in transitional cities.